Citizenship, democracy and social work - Schlingensiepen-Trint, Karina (Socialno delo, 2019)
In democratic constitutional states there is a gap between social inequalities as a result of capitalist societies and the status of free and equal citizens guaranteed by the constitution. This paper argues that social work, by "mediating" between the individual and society, is not only confronted with this gap. It can be shown that there is a direct link between social work, democracy and citizenship. The following hypotheses are laid out. (1) Social rights are the necessary condition for realizing the status of a free and equal active citizen. Social rights are necessary in order to achieve democratic conditions. (2) Taking into account the fact that rights are meaningless if there are no social conditions available for the individual to realize them, this paper argues that social rights implemented and guaranteed by a welfare state are needed but not sufficient. (3) The author points out that social work is crucial for the individual to really make use of his or her status as an equal free citizen and therefore for realizing democratic conditions. The paper ends with some consequences that arise from this theoretical consideration.
Keywords: demokracija; družbene razmere; država blaginje; državljanstvo; socialna politika; socialne pravice; socialno delo